Instytucjonalizacja pedagogiki w okresie Drugiej Rzeczypospolitej na przykładzie Katedry Pedagogiki i Dydaktyki Wszechnicy Piastowskiej - Nowak-Kluczyński, Konrad (Biuletyn Historii Wychowania, 2019)
The Second Polish Republic was a time of institutionalising and imposing stricter discipline in teaching in Poland. In the Interwar Period, institutions were established for teacher training, accompanied by new bodies in Polish universities tasked with teacher training and developing teaching methodology. A case in point was the establishment of the Faculty of Pedagogy and Didactics in Wszechnica Piastowska (Adam Mickiewicz University in Poznań). The first Faculty heads: Antoni Danysz, Bogdan Nawroczyński and Ludwik Jax-Bykowski, made considerable efforts for teacher training to play an important role in the structure of the Poznań University and to assume academic form. While the Faculty was closed down in 1933, Poznań University continued its cooperation with the Faculty of Psychology, thus providing an opportunity for educating future teachers.